Effects of Refining on the Characteristics of Suri Cucumber (Cucumis melo L. var. reticulatus Naudin) Seed Oil - Hartati Soetjipto; Laili Nurrohmah; Agustinus Ignatius Kristijanto (Chemistry Department, The University of Brawijaya, 2020)
The oil refining of Suri cucumber seed oil has been developed and tested. Crude oil was obtained by using soxhlet extraction in n-hexane, then was refined using chemical method by degumming and neutralization. This study aims are to determine the oil yield before and after refining, the oil’ physicochemical characteristic before and after refining and to determine the oil profile before and after refining by the Gas Chromatography-Mass Spectrometry (GCMS) method. The refining process cause the color of the oil become paler, but do not significantly affect on the water content and density. However, the process effect to decreasing of the acid value (5.547±0 mg NaOH/g oil to 0.5±0.14 mg NaOH/g oil) and the peroxide number (0.5077±0.036meq O2/g oil became 0.145 ± 0.036meq O2/g oil). Conversely, the saponification value increase (224.06±0.69mg KOH/g oil to 240.17±1.74mg KOH/g oil). GCMS analysis shows that refining process have effects on the composition of fatty acid in the oil.